An exploratory study of coach and players' emotion regulation in a female volleyball team - Kokkini, Eleana (2018)
Kokkini Eleana, 2018. An exploratory study of coach and players’ emotion regulation in a female volleyball team. Master’s Thesis in Sport and Exercise Psychology. Faculty of Sport and Health Sciences. University of Jyväskylä. 72p. During the past few decades, the strategies followed by athletes in order to initiate, maintain, modify or display emotions before and during competition have received extensive attention in sport settings (Gross and Thompson, 2007). The coach’s determinant role in the athlete’s pursuit of optimal performance is yet another topic of scientific interest (Chelladurai, 2007). The aim of the present study was to explore the emotion regulation strategies that Greek female volleyball players tend to follow before and during competition as well as the coach’s emotion awareness and contribution to the players’ regulation of emotion. The study’s sample consisted of ten Greek female volleyball players currently competing in the regional semi-professional championship of Western Greece and their coach. Data for both the players and the coach were collected using semi- structured interviews. Additional qualitative information was gathered through an observation protocol, which included the researcher’s descriptive and reflective notes. The collected data were thematically analyzed (Boyatzis, 1998). Themes and codes were developed using the inductive and deductive approach and the participants’ cues were compared to each other in search of similarities and differences between the players’ followed emotion regulation strategies and the coach’s awareness and interpersonal emotion regulation. The inductive and deductive analysis revealed eleven main themes for the players’ perceptions and emotion regulation strategies and eight main themes for the coach’s perceptions, emotion awareness and contribution to the players’ regulation of emotion. The results revealed that the participant players perceived pleasant emotions as more functional for their performance and described under which circumstances unpleasant emotions like stress turned from functional to dysfunctional. The players’ cues related to emotion regulation strategies supported the existing literature and disclosed self-talk, positive reappraisal, listening to music, putting into perspective, seeking others’ help and emotion sharing as the most frequent followed strategies. Interestingly, the results showed a high consistency between the coach’s and the players’ statements when compared. The coach was presented as an emotionally intelligent person who developed stable relationships in the team, was able to adapt in challenging situations and to manage the players’ emotions. The researcher’s observation notes supported the interview results. The study supported the existing literature and shed more light on the ongoing scientific flow regarding the integration of the emotion regulation (ER) and emotional intelligence (EI) traditions. Keywords: Coach-athlete relationship, emotion regulation, emotional intelligence, interpersonal emotion regulation, volleyball